The Effect of Airbag Design on Impact Attenuation for Hip Protection - Hongsakun, Thanaphon; Tangtrakulwanich, Boonsin; Vittayaphadung, Nitipan; Thongruang, Wiriya; Srewaradachpisal, Satta (Engineering, Technology & Applied Science Research, 2025)
This study examines the impact attenuation performance of airbags of different shapes, thicknesses, and internal pressures to assess their effectiveness in hip protection. Three distinct airbag shapes are examined and analyzed under different thicknesses and pressures, with experimental tests conducted to assess the relationships between thickness, pressure, stiffness, and impact absorption efficiency. The results reveal that increasing the thickness of the airbag significantly reduces the peak impact force, while higher internal pressure increases stiffness but does not always lead to improveδ impact attenuation. Among the three airbag shapes, the torus-shaped airbag demonstrates the lowest peak impact force and the highest impact absorption efficiency. Additionally, airbags maintained at atmospheric pressure (0 psi) exhibit the greatest impact absorption efficiency, followed by those at 3 psi and 6 psi, respectively. Comparing existing studies on traditional hip protectors, the results indicate that airbags provide a superior reduction in impact force. Unlike conventional hip protectors, which primarily rely on direct force absorption, the torus airbag employs an off-loading mechanism to dissipate impact energy, thereby enhancing its protective performance. These findings suggest that airbag-based protective systems could serve as an innovative solution for reducing fall-related injuries.